Cytoplasmic and Periplasmic Proteomic Signatures of Exponentially Growing Cells of the Psychrophilic Bacterium Pseudoalteromonas haloplanktis TAC125 - Wilmes, Boris (American Society for Microbiology (ASM), 2011)
The psychrophilic model bacterium Pseudoalteromonas haloplanktis is characterized by remarkably fast growth rates under low-temperature conditions in a range from 5°C to 20°C. In this study the proteome of cellular compartments, the cytoplasm and periplasm, of P. haloplanktis strain TAC125 was analyzed under exponential growth conditions at a permissive temperature of 16°C. By means of two-dimensional protein gel electrophoresis and mass spectrometry, a first inventory of the most abundant cytoplasmic and periplasmic proteins expressed in a peptone-supplemented minimal medium was established. By this approach major enzymes of the amino acid catabolism of this marine bacterium could be functionally deduced. The cytoplasmic proteome showed a predominance of amino acid degradation pathways and tricarboxylic acid (TCA) cycle enzymes but also the protein synthesis machinery. Furthermore, high levels of cold acclimation and oxidative stress proteins could be detected at this moderate growth temperature. The periplasmic proteome was characterized by a significant abundance of transporters, especially of highly expressed putative TonB-dependent receptors. This high capacity for protein synthesis, efficient amino acid utilization, and substrate transport may contribute to the fast growth rates of the copiotrophic bacterium P. haloplanktis in its natural environments.